Exploring the Nexus of lower extremity proprioception and postural stability in older adults with osteoporosis: a cross-sectional investigation - Ahmad, Irshad; Reddy, Ravi Shankar; Alqhtani, Raee S.; Tedla, Jaya Shanker; Dixit, Snehil; Ghulam, Hussain Saleh H.; Alyami, Abdullah Mohammed; Al Adal, Saeed; Jarrar, Mohammad A. M. (Frontiers in Public Health, 2023)
Background: Osteoporosis, characterized by reduced bone mass and micro-architectural deterioration, poses a significant public health concern due to increased fracture susceptibility. Beyond bone health, this cross-sectional study aimed to assess and compare lower extremity proprioception and postural stability in individuals with and without osteoporosis and to explore their correlation within the osteoporosis group.In this prospective cross-sectional study, 80 participants were divided into two groups: osteoporosis (n=40) and control (n=40). The demographic characteristics and clinical parameters of the participants were as follows: Age (years) -Osteoporosis group: 65.04 ± 4.